Optimization of ( ${R}$ , ${Q}$ ) Policies for Assembly Inventory Systems With Operating Flexibility - Peng Li; Di Wu (IEEE Access)
Guaranteed-Service Approach (GSA) was used to set safety stock for multi-echelon inventory systems. This approach assumes that each stock can use operating flexibility measures such as expediting and overtime to fulfill excessive customer demand superior to a bound as a supplement to its safety stock. In this paper, we consider a continuous review assembly inventory system with Poisson final demand and fixed order costs at each stock controlled by a ( $R$ , $Q$ ) policy. We use the GSA to optimize the policy with the consideration of operating flexibility costs and fixed order costs. A deterministic mathematical programming model is established for the problem. And the model is solved by a line search for finding the optimal target cycle service level (CSL) to customer and an iterative procedure for solving the model when the target CSL is given. Moreover, we analyze the optimality conditions for the extended GSA model and obtain some important properties in given conditions. Numerical experiments on randomly generated instances demonstrate the efficiency of the procedure and confirm the solution presented in this paper.